دراسة مقارنة تحليلية لشبكات المراقبة الارتفاعية في بعض السدود - أحمد محسن; فحصة إياد (Latakia University Journal -Engineering Sciences Series, 2016)
يهدف البحث إلى انجاز دراسة تحليلة نظرية وعملية للشبكات الارتفاعية في بعض السدود المتوسطة والصغيرة في المنطقة الساحلية من الجمهورية العربية السورية، من حيث شكل الشبكة ومتانتها والعناصر المقاسة، والأجهزة التي يجب استخدامها للحصول على الدقة المطلوبة، وكفاءة الموديل الرياضي المستخدم، وتصميم وتنفيذ نقاط التحكم والرصد في الشبكة المستخدمة واقتراح الحلول المناسبة. وخلال البحث تم انجاز برنامجين حاسوبيين مستقلين، يتعلق أولهما بنمذجة القياسات في شبكة تسوية محددة العناصر، والبرنامج الثاني يتعلق بإضافة برمجية لبرنامج الرسم الهندسي الشهير ( land development ) ليتمكن المستخدم من تعديل الشبكات الارتفاعية دون الخروج من البرنامج الرسومي. وقد خلص البحث إلى مقترحات محددة بشأن الشبكات الارتفاعية الجيوديزية المدروسة، وإلى إظهار كفاءة كل من البرنامج الحاسوبي المبني ضمن بيئة برنامج الرسم المساحي land development وبرنامج نمذجة القياسات الارتفاعية . The research aims to complete the theoretical, analytical and practical study for elevation networks in some medium and small dams in the coastal region of the Syrian Arab Republic, In terms of the configuration of network, strength of network and measured elements, And instruments that must be used to obtain the required accuracy, and efficient of the mathematical model used, The design and implementation of monitoring and control points in the used network and propose appropriate solutions. During the research was done on two independent programs , The first relates to simulated measurements in the elevation network specific elements, The second for adding program to software is the famous engineering drawing (land development) to enable the user for adjusting elevation networks without going out of the graphical program. The research concluded that specific proposals on elevation geodetic networks studied, and to show the efficiency of all programs designed within Land development software and modeling the elevation measurements.